Computer-aided design, synthesis and evaluation of new SARS-CoV-2 Mpro inhibitors based on 1,5,6,7-tetrahydro-4H-indazol-4-one scaffold - Piven, Yuri A.; Zinovich, Veronica G.; Shcherbakov, Dmitriy N.; Chirkova, Varvara Yu; Belenkaya, Svetlana V.; Puzanau, Raman M.; Khlebnicova, Tatyana S.; Lakhvich, Fedor A. (Medicinal chemistry research, 2024)
A novel class of SARS-CoV-2 main protease (M pro ) inhibitors derived from 1,5,6,7-tetrahydro-4 H -indazol-4-ones was designed. Virtual screening based on molecular docking followed by molecular dynamics simulation and MM/GBSA calculations was used for selecting compounds for synthesis and an evaluation. After testing 29 prepared compounds for activity against M pro , two hits with IC 50 values bellow 60 μM were found with the best result of 27.31 μM for racemic amide 9m . SAR and further possibilities for hit optimization were discussed. The effectiveness of different approaches (MM/GBSA and alchemical ABFE) for protein–ligand binding affinity prediction was assessed on the basis of obtained experimental data. The best convergence was achieved when we carried out long molecular dynamics simulations (200 ns) of complexes from docking followed by calculations of free binding energies with MM/GBSA method and explicit accounting of entropy.